Removal of arsenic from alkaline process waters of gold cyanidation by use of Fe3O4@SiO2@TiO2 nanosorbents - Feng, C.; Aldrich, C.; Eksteen, Jacques; Arrigan, Damien (Elsevier, 2017)
In this paper, the use of titania functionalised magnetic nanosorbents for rapid removal of arsenic from the alkaline process waters of gold cyanide leaching systems is considered. The Fe3O4@SiO2@TiO2 nanosorbent synthesised via a two-stage hydrolytic process was characterised by scanning electron microscopy - energy dispersive spectroscopy (SEM-EDS), X-ray diffraction (XRD), use of a superconducting quantum interference device (SQUID) and Brunauer-Emmett-Teller (BET) specific area methods. Batch adsorption tests showed that both As(III) and As(V) could be adsorbed onto the surface of nanosorbent in around 4 h, with the maximum adsorption capacity of 31.4 mg/g and 10.2 mg/g for As(III) and As(V), respectively, at pH 9. As demonstrated in competitive adsorption tests, the Fe3O4@SiO2@TiO2 nanosorbent performed well in simulated solutions of gold mining process waters with high ionic strengths and complex matrices, presenting a 21.3 mg/g integrated adsorption capacity for As(III) and As(V). The loss in capacity of the Fe3O4@SiO2@TiO2 nanosorbent after four consecutive adsorption-regeneration cycles was less than 40%. On the whole, the good arsenic adsorption capacity, easy preparation and magnetic separability coupled with reusability make it a potentially attractive material for the removal of arsenic from gold cyanidation process waters.